Gastric emptying during exercise - Maughan, R. J.; Rehrer, N. J. (1993)
1. Ingested drinks are retained in the stomach for a variable period of time, and the rate of gastric emptying may limit the replacement of carbohydrate and water during exercise. 2. High intensity exercise will slow or even stop gastric emptying, but exercise at intensities up to about 70-75% of maximal oxygen uptake has little or no effect on the rate of gastric emptying. 3. Increasing energy content will slow gastric emptying, and the pattern during exercise is the same as that observed at rest. Emptying is also slowed by solutions with very high osmolality relative to that of body fluids. 4. There is a large variation among individuals in the rate of gastric emptying. 5. Factors such as weather conditions may influence the choice of drinks. 6. Athletes should experiment during training to establish how much fluid they need and can tolerate.